THE FIRST INFORMATION ABOUT MORMONS IN THE RUSSIAN PERIODICALS (1850–1857) - Prilutskiy V.V. (Вестник Брянского государственного университета)
The article examines the first information about the Mormons (the Church of Jesus Christ of Latter-day Saints) in Russia, contained in messages, notes and articles in the periodical press (1850–1857). The unique phenomenon of the Mormons and their successful development of vast territories in the Great Salt Lake and Rocky Mountains attracted the attention of contemporaries not only in the United States, but also in other countries. An analysis of information about the religious organization, its features, main ideas, emergence, history and prospects contained in the Russian periodicals was carried out. It is shown that the first domestic researchers provided mostly reliable information about early Mormonism. The Mormon religious movement was founded by the Prophet Joseph Smith, Jr. (1805-1844) in western New York in 1830. Tens of thousands of supporters joined the new religious movement in the 1830s and 1840s, including numerous converted immigrants from Canada and Western Europe. Domestic journalists and publicists noted that Mormons were constantly persecuted and forced to migrate to the Western United States. After the death of the first prophet at the hands of local militias in 1844, they were led by Brigham Young (1801-1877). In 1847, under his leadership, the migration of Mormons to Western America began on the territory of Utah, where they created a quasi-state entity that existed until the 1890s. In the Russian periodical press in the 1850s, along with reliable information, there were also ridiculous rumors, unfounded assumptions, myths, distorted and sometimes completely false information about Mormons. This was largely due to the inconsistency of the early history of the Mormons and the unverified data about them that was distributed in American and European journalism of the XIXth century.